Identification of a PDZ-domain-containing protein that interacts with the scavenger receptor class B type I - Ikemoto, Mamoru (National Academy of Sciences, 2000)
The scavenger receptor class B type I (SR-BI) mediates the selective uptake of cholesteryl esters from high-density lipoprotein (HDL) and cholesterol secretion into bile in the liver. In this study, we identified an SR-BI-associated protein from rat liver membrane extracts by using an affinity chromatography technique. This protein of 523 amino acids contains four PDZ domains and associates with the C terminus of SR-BI by using its N-terminal first PDZ domain. Therefore, we denoted this protein as CLAMP (C-terminal linking and modulating protein). CLAMP was located mostly in the sinusoidal membranes, whereas SR-BI was detected in both sinusoidal and canalicular membranes. After the solubilization of the liver membranes with Triton X-100, SR-BI was immunoprecipitated with anti-CLAMP monoclonal antibody, suggesting the association of these proteins in vivo. By coexpressing SR-BI with CLAMP in Chinese hamster ovary cells, we observed (i) the increase in the expression level of SR-BI, (ii) the reduction in the deacylation rate of the cholesteryl esters taken up from HDL, and (iii) the change in the intracellular distribution of fluorescent lipid 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindocarbocyanine percholate taken up from HDL. Taken together, these data suggest that CLAMP, a four-PDZ-domain-containing protein, is associated with SR-BI in the liver sinusoidal plasma membranes and may modulate the intracellular transport and metabolism of cholesteryl esters taken up from HDL.